PENENTUAN FASIES DAN ARUS PURBA BERDASARKAN KETERDAPATAN STRUKTUR SEDIMEN DAN LITOLOGI PADA KECAMATAN NGLIPAR, KABUPATEN GUNUNG KIDUL, YOGYAKARTA - rizqi, al hussein flowers; Thabita Monica Tupang, Kannaya; Qoyyibi, Dava Saliham; Gil Lodar, Jaden (ReTII, 2025)
Research on paleocurrent directions in the Oyo Formation remains limited. Sedimentary structures used in determining paleocurrent directions can be observed in the Kali Oyo area, Nglipar District, Gunung Kidul Regency, Special Region of Yogyakarta, which serves as the study area. In this area of investigation, rock outcrops with a total measured stratigraphic thickness of 10.7 meters were identified, which is considered sufficiently representative for paleocurrent analysis. The objective of this study is to compile research findings by obtaining data on sedimentary structures and lithological variations along the measured stratigraphic section. Based on field observations, the lithology consists of calcilutite limestone, calcarenite limestone, and calcirudite limestone, while the sedimentary structures used to determine paleocurrent directions include slump structures and cross-bedding. Based on the collected data, facies and paleocurrent direction analyses were conducted. The area is interpreted to represent foreslope and winnowed edge sand facies, with the observed paleocurrent patterns being bipolar and polymodal. Keyword : Oyo Formation, Paleo Currents, Facies. Gunung Kidul